2020
DOI: 10.2298/jmmb190225019w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lance height and angle on the penetration depth of inclined coherent and conventional supersonic jets in electric arc furnace steelmaking

Abstract: Nowadays, coherent and conventional supersonic jets are widely used in electric arc furnace (EAF)steelmaking processes. Generally, these jets are installed in the EAF oven wall with a tilt angle of 35-45?. However, limited studies have been conducted on the impact characteristics of these inclined supersonic jets. This study developed an optimized theoretical model to calculate the penetration depth of inclined coherent and conventional supersonic jets by combining theoretical modeling and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Other [1,7,11,12,16,22,[25][26][27][28][29][30] • • [2,6,14,23,24,[31][32][33][34][35][36][4] • • [13,[37][38][39][17,18] • • [19][20,21,40,41] •…”
Section: Coherent Jetmentioning
confidence: 99%
See 1 more Smart Citation
“…Other [1,7,11,12,16,22,[25][26][27][28][29][30] • • [2,6,14,23,24,[31][32][33][34][35][36][4] • • [13,[37][38][39][17,18] • • [19][20,21,40,41] •…”
Section: Coherent Jetmentioning
confidence: 99%
“…Additionally, the corresponding impacted-O2 molar flow rates at these positions are 24 mol/s, 14 mol/s, and 9 mol/s, respectively. Furthermore, the penetration depth of the inclined jet, determined by applying the theoretical model equation described in Wu et al research [30], is presented in Table 3. For Case A3, the penetration depth at a nozzle-to-molten metal distance of 1000 mm is 389 mm.…”
Section: Prediction Of Jet Penetration At Impact Zonementioning
confidence: 99%
“…Для исследования динамического взаимодействия многофазных систем часто используют численное моделирование происходящих процессов [22,24,[26][27][28]. Такой подход позволяет изучить изменение модулей и направлений векторов скоростей потоков во всех точках модели рассматриваемой двухфазной системы, однако результаты численного моделирования, в свою очередь, требуют обобщения информации, полученной об исследуемой системе.…”
Section: теоретический анализunclassified
“…В работе [20] представлены результаты численного моделирования переходного процесса, возникающего в системе " струя газа − жидкость" при ступенчатом перпендикулярном аэродинамическом воздействии (вязкость жидкости ∼ 1 Pa•s). Взаимодействие неперпендикулярной газовой струи с поверхностью жидкости исследовано в работах [3,[23][24][25][26]. В этих публикациях использованы невязкие жидкости (Re > 100).…”
Section: Introductionunclassified
“…Wei et al 10 combined a theoretical model and numerical simulation to establish a hybrid model for predicting the penetration depth of a coherent supersonic jet, and the error is < 3.92%. Wu et al 11 used a theoretical model and numerical simulation to establish an improved model for the penetration depth of an inclined coherent jet. Cao et al 12 proposed a cavity shape index to quantitatively characterise the cavity shape, and it was found that there is an exponential relationship between the index and the splashing rate of molten steel.…”
Section: Introductionmentioning
confidence: 99%